PENDIDIKAN UNTUK MENYAMBUT MASYARAKAT 5.0 - Rohim, Herli; Darwanto, Darwanto (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstractâ€”The development of the world of education is entering a very important period. Not only in an effort to provide quality and optimal education services. But it is also an important period that will determine the continuation of education itself. Today, the challenges in education are increasingly complex and require very serious preparation and thinking. We are faced with a rapid and non-linear change. This is as a result of the rolling of the Industrial Revolution 4.0 era. These technological advancements enable automation in almost all fields. As we know, the first generation industrial revolution was marked by the use of steam engines to replace human and animal power. The second generation, through the application of the concept of mass production and the use of electricity. The third generation, marked by the use of automation technology in industrial activities. In the fourth industrial revolution, it became a big leap for the industrial sector, where information and communication technology was fully utilized. The hustle and bustle of the Industrial Revolution 4.0, which was accompanied by the development of a disruption era, was suddenly shocked by the emergence of Society 5.0 (community 5.0). The concept of Society 5.0 has actually been rolling for a long time. This concept appears in the "Basic Policy on Economic and Fiscal Management and Reform 2016" which is a core part of the strategic plan adopted by the Japanese Cabinet, January 2016. The concept of Society 5.0 was adopted by the Japanese Government in anticipation of global trends as a result of the emergence of the Industrial Revolution 4.0. Society 5.0 is a natural thing that must have happened due to the rise of the Industrial Revolution 4.0. The Industrial Revolution 4.0 has given birth to various innovations in the industrial world and also society in general. Society 5.0 is the answer to the challenges that arose as a result of the Industrial Revolution 4.0 era accompanied by disruption characterized by a world of turmoil, uncertainty, complexity, and ambiguity. Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations that were born in the era of the Industrial Revolution 4.0 such as the Internet on Things (artificial internet), Artificial Intelligence, Big Data (large amounts of data), and robots to improve the quality of human life. Society 5.0, a time in which human-centered societies balance economic progress with the resolution of social problems by systems that integrate cyberspace and physical space. Society 5.0 will balance economic development and solve social problems.Â Keywordâ€” Society 5.0 will balance economic development and solve social problems.Â Abstrakâ€”Perkembangan dunia pendidikanÂ tengah memasuki masa yang sangat penting. Tidak saja dalam upaya memberikan pelayanan pendidikan yang berkualitas dan optimal. Tetapi juga masa penting yang akan menentukan kelanjutan pendidikan itu sendiri.Â Saat ini, tantangan dunia pendidikan semakin kompleks dan menuntut persiapan dan pemikiran yang sangat serius. Kita dihadapkan pada suatu perubahan yang cepat danÂ non-linear. Ini sebagai akibat bergulirnya era Revolusi Industri 4.0. Kemajuan teknologi ini memungkinkan otomatisasi di hampir semua bidang.Â Sebagaimana kita tahu revolusi industri generasi pertama ditandai oleh penggunaan mesin uap untuk menggantikan tenaga manusia dan hewan. Generasi kedua, melalui penerapan konsep produksi massal dan mulai dimanfaatkannya tenaga listrik. Generasi ketiga, ditandai dengan penggunaan teknologi otomasi dalam kegiatan industri. Pada revolusi industri keempat, menjadi lompatan besar bagi sektor industri, di mana teknologi informasi dan komunikasi dimanfaatkan sepenuhnya. Belum usai hiruk-pikuk akibat Revolusi Industri 4.0, yang dibarengi berkembangan era disrupsi, tiba-tiba kita dikejutkan dengan munculnya Society 5.0 (masyarakat 5.0). Konsep Society 5.0 sebenarnya sudah bergulir cukup lama. Konsep ini muncul dalam â€œBasic Policy on Economic and Fiscal Management and Reform 2016â€ yang merupakan bagian inti dari rencana strategis yang diadopsi Kabinet Jepang, Januari 2016. Konsep Society 5.0 diadopsi Pemerintah Jepang sebagai antisipasi terhadap tren global sebagai akibat dari munculnya Revolusi Industri 4.0. Society 5.0 adalah hal alami yang pasti terjadi akibat munculnya Revolusi Industri 4.0. Revolusi Industri 4.0 telah melahirkan berbagai inovasi dalam dunia industri dan juga masyarakat secara umum. Society 5.0 merupakan jawaban atas tantangan yang muncul akibat era Revolusi Industri 4.0 yang dibarengi disrupsi yang ditandai dunia yang penuh gejolak, ketidakpastian, kompleksitas, dan ambiguitas. Society 5.0 adalah masyarakat yang dapat menyelesaikan berbagai tantangan dan permasalahan sosial dengan memanfaatkan berbagai inovasi yang lahir di era Revolusi industri 4.0 sepertiÂ Internet on ThingsÂ (internet untuk segala sesuatu),Â Artificial IntelligenceÂ (kecerdasan buatan),Â Big DataÂ (data dalam jumlah besar), dan robot untuk meningkatkan kualitas hidup manusia. Society 5.0, sebuah masa di mana masyarakat berpusat pada manusia yang menyeimbangkan kemajuan ekonomi dengan penyelesaian masalah sosial oleh sistem yang mengintegrasikan ruang dunia maya dan ruang fisik. Society 5.0 akan menyeimbangkan pembangunan ekonomi dan menyelesaikan masalah sosial.Â Kata kunciâ€” Society 5.0 akan menyeimbangkan pembangunan ekonomi dan menyelesaikan masalah sosial.Â